Use of naproxen versus intracervical block for pain control during the 52-mg levonorgestrel-releasing intrauterine system insertion in young women: a multivariate analysis of a randomized controlled trial - Elaine Cristina Fontes de Oliveira; Thaís Baêta; Ana Paula Caldeira Brant; Agnaldo Silva-Filho; Ana Luiza Lunardi Rocha (BMC, 2021)
Abstract Background To compare the effectiveness of 550 mg naproxen sodium versus 6 mL 2%-lidocaine intracervical block in pain lowering at the 52-mg levonorgestrel-releasing intrauterine system (LNG-IUS) placement in young women. Methods In this randomized controlled trial, 100 women aged 15-24 years were block-randomized to receive either 6 mL 2%-lidocaine intracervical block 5 min before the LNG-IUS insertion or 550 mg naproxen 30 min before the procedure. Forty-nine women received 550 mg naproxen and 51 received intracervical block. The primary outcome was pain at LNG-IUS insertion. Secondary outcomes were ease of insertion, insertion failures, and correct IUS positioning. Neither participants nor doctors were blinded. Pain at insertion was assessed by using a Visual Analog Scale (VAS). Results Women randomized to lidocaine intracervical block presented lower mean pain score at insertion, when compared to women who received naproxen (5.4 vs. 7.3, respectively; p < 0.001). Parous women had a 90.1% lower chance of experiencing severe pain (p = 0.004). There was a 49.8% reduction in the chance of severe pain for every 1-cm increase in the hysterometry (p = 0.002). The only complication observed during insertion was vasovagal-like reactions (7%). The insertion was performed without difficulty in 82% of the women. Participants in the intracervical block group presented higher proportion of malpositioned IUS on transvaginal ultrasound examination compared to women in naproxen group. Nevertheless, all the malpositioned IUS were inserted by resident physicians. Conclusion Lidocaine intracervical block was found to be more effective than naproxen in reducing LNG-IUS insertion pain. Trial registration number: RBR-68mmbp, Brazilian Registry of Clinical Trials, Retrospectively registered (August 4, 2020), URL of trial registry record: https://ensaiosclinicos.gov.br/rg/RBR-68mmbp/ .